PENGUATAN KARAKTER SISWA MELALUI BAHASA INDONESIA YANG BAIK DAN BENAR PADA GENERASI MILENIAL DI DESA CIARUTEUN UDIK KECAMATAN CIBUNGBULAN KABUPATEN BOGOR - Nina; Resya Fathrunisa; M. Ichsan Nurjam’an; Siti Risma Adawiyah; Ridha Meidina Putri; Mia Amalia; Muhammad; Muhammad Bella Akbar; Tri Hayatul Lutfi; Dede Sumiati; Irma Suriyani (STKIP Muhammadiyah Bogor, 2023)
Education has a big contribution to the sustainability of a person’s quality, apart from that character education must also be instilled in a person, to advance the quality and achievement of character formation in students which leads to educational outcomes in schools, teachers have a very important role in directing their students to continue to use good and correct Indonesian. Especially in the school environment. However, the development of digital technology is increasingly advanced and as time goed by, Indonesian is starting to be forgotten and its position is weakening as the national language. Therefore, KKN-Dik participants held language seminars with the theme “Strengthening Student Character Through Good and Correct Indonesian in Milllennial Generation” as a form of serving and empowering the community, especially students. This seminar was held on Thursday, 213 February 2023 at Al-Kahfi Vocational School Ciaruten Udik Village, with the enthusiasm of the seminar participants, totaling 20 students and female students. This seminar is expected to provide knowledge, benefits for seminar participants, especially in the fields of education and language.